The usage of humour elements in instructional communication and their roles in students' achievement - Zaharim, Ziyad Afiq; Adzharuddin, Nor Azura (Global Academy of Training & Research (GATR) Enterprise, 2015)
Objective – The purpose of this article is to examine the usage of humour elements through the learning process in lectures and how these influence the achievements among university students. Apart from that, this article is to justify several questions that includes: To examine the humorous elements involved in learning and communication process while attending lectures, to investigate the type of humour and their appropriateness when used for instructional communication, and finally, to examine the relationship between the usage of humour elements and the achievements among higher education students.